2018
DOI: 10.1590/0100-3984.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Integrating bilingual musculoskeletal imaging education into radiology and diagnostic imaging residency programs

Abstract: ObjectiveTo analyze the perception of the relevance of introducing bilingual (Portuguese-English) musculoskeletal imaging education into radiology and diagnostic imaging residency programs, describing the method used.Materials and MethodsTo evaluate the relevance of incorporating the bilingual study of musculoskeletal imaging into medical residency programs, we administered a questionnaire, consisting of several multiple-choice questions and one subjective question, to 21 radiology residents at a private terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In Morocco, the use of the mother tongue in teaching medicine was considered as an educational necessity [26], some efforts were made to introduce bilingual programs [2].…”
Section: Proficiency In the English Language Can Pose Serious Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In Morocco, the use of the mother tongue in teaching medicine was considered as an educational necessity [26], some efforts were made to introduce bilingual programs [2].…”
Section: Proficiency In the English Language Can Pose Serious Problemmentioning
confidence: 99%
“…While higher education faculties and institutions usually use English as the main teaching language. Therefore, this linguistic disparity often impairs students' learning abilities and generate low self-image if they are not fluent in English [2]. Besides, some studies have shown that students tend to stress when they study in a foreign language [3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a bilingual approach using both English and vernacular languages as the medium of instruction could be one practical approach, as highlighted by a participant of workshop 1 at the brainstorming session (Table 6). Besides better understanding of the subject, this approach has the possibility of promoting increased communication skills among healthcare providers and end-users (1,4,12).…”
Section: Useful Lessons From the Workhop Seriesmentioning
confidence: 99%